What is read and written in Colombian university? Characterization of literacy practices in 17 universities - Mauricio Pérez Abril; Alfonso Rodríguez Manzano (Universitat Politècnica de València, 2013)
The purpose of the research What is read and written in Colombian university? A contribution to the consolidation of the academic culture of the country was to characterize the literacy practices prevailing in Colombian university. It was a descriptive and interpretive study based on quantitative and qualitative data. We studied 17 universities. Five sources were analyzed: a) survey to students; b) courses that universities offer to support reading and writing processes, c) institutional policy documents, d) focus groups of students, teachers and researchers; e) 17 case studies of outstanding practices. The overall results indicate that universities do dedicate to strengthening the processes of academic reading and writing, mainly offering literacy courses as generic skills, but not as specific disciplinary epistemic practices. The class notes are the most read and written text in most careers, indicating that for students that particular form of appropriation of knowledge which distributes college is a priority, rather than its use in academic and practical fields application. The analysis of outstanding practices shows that for these teachers, reading and writing are more effects and conditions of a position on knowledge than ends in themselves. This article is a summary of the research and a selection and discussion of some key results.